1995
DOI: 10.1002/ijc.2910640511
|View full text |Cite
|
Sign up to set email alerts
|

MDM2 gene amplification in bone and soft‐tissue tumors: Association with tumor progression in differentiated adipose‐tissue tumors

Abstract: We have studied 107 bone and soft-tissue sarcomas and 8 lipomas for amplification of the MDM2 gene. This gene was amplified in 3 out of 67 osteosarcomas, 3 out of 20 malignant fibrous histiocytomas, 4 out of 20 liposarcomas, and 4 out of 8 lipomas. The amplification was associated with overexpression of mRNA. In osteosarcomas, contrary to previous findings, all amplifications were observed in primary lesions. In liposarcomas, the amplification was seen exclusively in well-differentiated tumors with high freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
81
0
2

Year Published

1997
1997
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(86 citation statements)
references
References 13 publications
3
81
0
2
Order By: Relevance
“…For example, Oliner et al, (1992) reported ampli®cation of MDM2 in 3/11 (27%) cases of OSA; however, others have identi®ed MDM2 ampli®cation in only 4 ± 7% of cases (Nakayama et al, 1995;Miller et al, 1996;Lonardo et al, 1997). We found SAS ampli®ed in 6/6 parosteal OSA and 2/16 intramedullary tumors.…”
Section: Discussionmentioning
confidence: 45%
“…For example, Oliner et al, (1992) reported ampli®cation of MDM2 in 3/11 (27%) cases of OSA; however, others have identi®ed MDM2 ampli®cation in only 4 ± 7% of cases (Nakayama et al, 1995;Miller et al, 1996;Lonardo et al, 1997). We found SAS ampli®ed in 6/6 parosteal OSA and 2/16 intramedullary tumors.…”
Section: Discussionmentioning
confidence: 45%
“…20,25,26,29,37 Scoring as positive only those normal and neoplastic lesions, such as in uterine cases showing at least 3-fold amplification (MDM2 smooth muscle tumors and as a prognostic indicator copy number ú 6), very similar figures were reported in malignancies, such as soft tissue tumors 45 and by Nakayama et al (4.5%; n Å 67) 25 and Miller et al…”
Section: Discussionmentioning
confidence: 71%
“…27 Amplification of MDM2 has been associated with recurrent or metastasic OS in some studies, 26 but not in others. 25 …”
mentioning
confidence: 99%
“…It has been reported that over 50% of osteosarcomas have a LOH at the Rb locus, and a higher probability of metastasis has been observed in patients with loss of pRb (Wadayama et al, 1994;Benassi et al, 1999). The event-free survival rate at 60 months is 100% for patients without LOH, 43% for all patients with Rb LOH and 65% for non-metastatic patients with Rb LOH (Feugeas et al, 1996).…”
Section: Sarcomasmentioning
confidence: 99%